1995
DOI: 10.1159/000109778
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Duplication at 17p11.2 in Families of Northeast Italy with Charcot-Marie-Tooth Disease Type 1

Abstract: Charcot-Marie-Tooth disease type 1 (CMT1) is the most common form of the hereditary motor sensory neuropathies (HMSN) with a prevalence in the Italian population of 9.4/ 100,000 inhabitants. CMT 1 is a genetically heterogeneous disorder. Forty CMT 1 families (35 with recurrence of cases and 5 sporadic cases) living in northeastern Italy were analyzed with the probe pVAW409R3 to reveal the presence of 17p11.2 duplication. The duplication frequency that resulted was about 82% and not significantly different in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…This is even more so for studies based on genetic analysis. Mostacciuolo [3] reported a 9.4/100,000 prevalence rate of CMT1 cases in Northern Italy with an 82% rate for CMT1A. Holmberg et al [4] found a prevalence rate of 16.2/100,000 for CMT1A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is even more so for studies based on genetic analysis. Mostacciuolo [3] reported a 9.4/100,000 prevalence rate of CMT1 cases in Northern Italy with an 82% rate for CMT1A. Holmberg et al [4] found a prevalence rate of 16.2/100,000 for CMT1A.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold conduction velocity distinguishing the two forms is considered as being 38 m/s for the median nerve, but overlapping values have been reported [2]. Type 1 is the most prevalent form, accounting for about 80% of the cases of CMT [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding epidemiological studies, most have investigated the prevalence of general CMT; most of the remaining studies have investigated the prevalence of CMT1, the most common subtype of the disease [18]. Prevalence studies evaluating only CMT2 are rare.…”
Section: Discussionmentioning
confidence: 99%
“…ters have been published elsewhere [9,39,[46][47][48][49][50][51][52][53][54]. Only 6 out of 579 (1.0%) patients were found to have a smaller duplication.…”
Section: Mutation Analysismentioning
confidence: 99%